A facile synthesis of polythiophene nanowires - Karim, M.R.; Lima, K.T.; Lee, C.J.; Lee, M.S.
Polythiophene nanowires have been synthesized by the gamma radiation-induced chemical oxidative polymerization method. The resultant fiber-like polymer structures were identified by the field-emission scanning electron microscopy with diameter of the order of 50-100 nm and a length of up to several millimeters. Different characterizations, e.g. elemental analysis, Fourier transform infrared, Raman spectroscopy, and X-ray photoelectron microscopy were utilized to prove that conducting polythiophene was synthesized successfully by this facile method.
Keywords: CONJUGATED POLYMERS; NANOPARTICLES; RADIOLYSIS POLYMERIZATION; FACILE SYNTHESIS